2003
DOI: 10.1046/j.1365-2141.2003.04578.x
|View full text |Cite
|
Sign up to set email alerts
|

Veno‐occlusive disease in patients receiving thiopurines during maintenance therapy for childhood acute lymphoblastic leukaemia

Abstract: Summary. The case records of 99 consecutive children with acute lymphoblastic leukaemia who received either 6-thioguanine (6-TG) or 6-mercaptopurine (6-MP) as maintenance therapy for at least 1 year were reviewed for hepatic veno-occlusive disease (VOD). Overall, 12% of those on 6-TG developed VOD (all boys). Isolated persistent thrombocytopenia appeared to be the earliest indicator of incipient VOD. Multivariate analysis identified male sex and 6-TG as risk factors. In all cases, VOD was mild and reversible o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 7 publications
3
61
0
Order By: Relevance
“…Thiopurines are associated with hepatotoxicity; hepatic transaminase elevations have been related to MeTIMP concentrations after mercaptopurine (48) whereas hepatic veno-occlusive disease is more common after thioguanine than mercaptopurine and seems to be dose related (49). Our data are consistent with the hypothesis that TPMT may contribute to hepatocellular toxicity via methylation of mercaptopurine metabolites (43,45,50) but does not relate to thioguanine hepatotoxicity: we did not observe transaminasemia after thioguanine regardless of Tpmt genotype.…”
Section: Discussionsupporting
confidence: 81%
“…Thiopurines are associated with hepatotoxicity; hepatic transaminase elevations have been related to MeTIMP concentrations after mercaptopurine (48) whereas hepatic veno-occlusive disease is more common after thioguanine than mercaptopurine and seems to be dose related (49). Our data are consistent with the hypothesis that TPMT may contribute to hepatocellular toxicity via methylation of mercaptopurine metabolites (43,45,50) but does not relate to thioguanine hepatotoxicity: we did not observe transaminasemia after thioguanine regardless of Tpmt genotype.…”
Section: Discussionsupporting
confidence: 81%
“…5 As a consequence, 6-MP has remained the preferred drug for maintenance therapy. Veno-occlusive disease, as reported in other studies, 21,22 did not occur in COALL patients. This was also true for trial ALL-REZ 90 for relapsed patients, in which 6-TG was used together with weekly intravenous MTX in maintenance therapy (G Henze, personal communication).…”
Section: Discussionsupporting
confidence: 63%
“…41 In our study and in that of the UK MRC, VOD or DT correlated with longer duration of exposure and higher cumulative dose of TG. 27,42 Data from the latter study, and from the CCG-1942 intravenous TG pilot study, showed no temporal correlation between high plasma levels of TGNs or TG and episodes of VOD. 27,31,32,43 Considering the extensive first-pass intestinal and hepatic metabolism that follows oral dosing of TG, VOD likely reflects damage of sinusoidal endothelium caused directly by parent compound or a hepatic metabolite(s) not formed from MP.…”
Section: Discussionmentioning
confidence: 99%
“…Both VOD and DT occurred in patients receiving TG on the UK MRC protocols, despite the lower starting dose of 40 mg/m 2 . 26,27 No VOD was reported on the German Cooperative Study Group COALL study, with TG doses of 40 to 50 mg/m 2 . However, patients on TG had a 7.5-fold higher incidence of thrombocytopenia without neutropenia than those on MP, 25 similar to the DT described in our study.…”
Section: Discussionmentioning
confidence: 99%